Physical Activity in the Prevention of Childhood Obesity: The Position of the European Childhood Obesity Group and the European Academy of Pediatrics - Wyszyńska, Justyna; Ring-Dimitriou, Susanne; Thivel, David; Weghuber, Daniel; Hadjipanayis, Adamos; Grossman, Zachi; Ross-Russell, Robert; Dereń, Katarzyna; Mazur, Artur (Frontiers in Pediatrics, 2020)
Obesity affects an increasing number of children and adolescents. Physical activity (PA) is a significant factor in the prevention of excessive body mass in the pediatric population. A significant percentage of pediatric population do not attain the public health recommendation for PA, and typically, those with higher levels of PA have lower content of body fat than less active peers. Although the development of childhood obesity is multifactorial, the decline in energy expenditure is considered as one of the most important determinants of excessive body weight. The lack of intervention causes that excess body weight to remain stable from birth through childhood and adolescence to adulthood. Accordingly, public health interventions are needed to increase the level of PA in the pediatric population. The task force from the European Childhood Obesity Group and the European Academy of Pediatrics reviewed English language meta-analyses, systematic reviews, randomized clinical trials, and observational studies from PubMed/MEDLINE, Cochrane Library, Science Direct, MEDLINE, and EBSCO databases, from 2018 to August 2020, and developed a consensus statement. This statement presents the role of PA in the prevention of excessive body weight and gives age-appropriate recommendations for PA and recommendations for school-based interventions, parents, and guardians.